Reexamining Kautilya and Machiavelli: Flexibility and the Problem of Legitimacy in Brahmanical and Secular Realism. (December 2014) - Gray, Stuart
Since the rediscovery of the ancient Indian political thinker Kautilya and his Arthaśāstra in the early twentieth century, scholars have argued for similarities between his political thinking and Machiavelli's, especially on the topic of realism. Employing a new analytic approach to reexamine their political thought, I locate unidentified tensions and overlaps between Machiavelli's secular ethic, which pulls towards autonomous standards, and Kautilya's political-theological ethic, which follows traditional brahmanical beliefs. In the first part of the essay, I challenge existing interpretations of Kautilya's thought and clarify a coherent political theology in the Arthaśāstra . The second part critically assesses their realist positions using the concepts of flexibility and legitimacy. While I explain how the Machiavellian position poses justifiable objections to the apparent repression and self-defeating nature of brahmanical realism, I also argue that the Kautilyan position raises important questions concerning both the flexibility and inflexibility of a secular realist position.